Preparation process of blowout preventer rubber core with excellent corrosion resistance

By using vinyl-terminated RTV-615 prepolymer in polydimethylsiloxane solution in blowout preventer core to form a crosslinking structure with hydrogenated nitrile rubber, hydrogenated nitrile rubber in hydrogen sulfide environment is solved The problem of aging and degradation has significantly improved its corrosion resistance and wear resistance.

CN119119520AActive Publication Date: 2024-12-13RIZHAO CHENHUI RUBBER&PLASTICS PROD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411507334.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-13
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Hydrogenated nitrile rubber aging and degrading in a hydrogen sulfide corrosion environment, resulting in insufficient corrosion resistance, affecting the service life of the blowout preventer core.

Method used

The vinyl-terminated RTV-615 prepolymer in polydimethylsiloxane solution is used to form a cross-linked structure with the acrylonitrile groups in hydrogenated nitrile rubber to form a dense network structure to reduce the permeation of hydrogen sulfide and Reaction to improve the corrosion resistance of hydrogenated nitrile rubber.

Benefits of technology

It significantly improves the corrosion resistance of hydrogenated nitrile rubber, enhances its stability and wear resistance in high temperature and corrosive environments, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of rubber, and particularly discloses a preparation process of a blowout preventer rubber core with excellent corrosion resistance. The preparation method of the blowout preventer rubber core with excellent corrosion resistance comprises the following steps: weighing butyronitrile latex and stirring; deionized water is added for stirring, and then a defoaming agent is added; sequentially adding anhydrous cupric sulfate, lauryl sodium sulfate and hydrazine hydrate; dropwise adding hydrogen peroxide, and after the hydrogen peroxide is completely dropwise added, continuing the reaction in the test to obtain hydrogenated butyronitrile latex; placing the hydrogenated nitrile rubber latex in a water bath environment, and adding a calcium chloride solution to obtain flocculated hydrogenated nitrile rubber; soaking the flocculated hydrogenated butadiene-acrylonitrile rubber in deionized water, taking out and airing to obtain hydrogenated butadiene-acrylonitrile rubber; the preparation method comprises the following steps: completely immersing hydrogenated butadiene-acrylonitrile rubber into a polydimethylsiloxane solution, taking out the immersed hydrogenated butadiene-acrylonitrile rubber, hanging and airing in a ventilated place, and curing in a drying oven to obtain the modified hydrogenated butadiene-acrylonitrile rubber. The blowout preventer rubber core with excellent corrosion resistance has the advantage of excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of rubber technology, and more specifically, to a process for preparing a blowout preventer rubber core with excellent corrosion resistance. Background Art

[0002] A blowout preventer is a device used to close the wellhead and prevent blowout accidents during operations such as oil testing, well repair and completion. It has the characteristics of simple structure, easy operation and high pressure resistance. It is a safety sealing wellhead device commonly used in oil fields to prevent blowouts. The key component inside the blowout preventer when in use is the rubber core. When in use, the rubber core is restricted by the top cover and cannot move upward. Under the action of the inner cone surface of the piston, it is forced to squeeze and shrink toward the center of the wellbore until the hollow part of the rubber core is filled with rubber, thereby achieving the purpose of fully sealing the wellhead.

[0003] As oil exploration drilling becomes deeper and deeper, more and more oil and gas wells containing hydrogen sulfide are discovered. Hydrogen sulfide is corrosive, so in order to prevent the rubber core from being corroded by hydrogen sulfide, hydrogenated nitrile rubber is usually used. Hydrogenated nitrile rubber is a heat-resistant and oil-resistant elastomer made by hydrogenating nitrile rubber. Since the molecular structure of hydrogenated nitrile rubber contains fewer or no carbon-carbon double bonds, it not only has the oil resistance and wear resistance of nitrile rubber, but also has improved weather resistance and chemical stability compared to nitrile rubber. In addition, it also has higher strength that most oil-resistant rubbers do not have. In particular, its high temperature resistance is greatly improved compared to nitrile rubber. However, excessive content of acrylonitrile groups in hydrogenated nitrile rubber will also react with hydrogen sulfide to form thioamides, which will lead to aging and degradation of hydrogenated nitrile rubber, thereby affecting the corrosion resistance of hydrogenated nitrile rubber. Summary of the invention

[0004] In order to improve the defect that the corrosion resistance of hydrogenated nitrile rubber is still insufficient, the present application provides a process for preparing a blowout preventer rubber core with excellent corrosion resistance.

[0005] The present application provides a blowout preventer rubber core with excellent corrosion resistance, which adopts the following technical solution: A process for preparing a blowout preventer rubber core with excellent corrosion resistance comprises the following steps: S1: Weigh nitrile latex and stir; S2: Add deionized water and stir, then add defoamer; S3: adding anhydrous copper sulfate, sodium dodecyl sulfate, and hydrazine hydrate in sequence; S4: adding hydrogen peroxide dropwise, and after the hydrogen peroxide is completely added, the test continues to react to obtain hydrogenated nitrile latex; S5: placing the hydrogenated nitrile latex in a water bath environment, adding a calcium chloride solution, and obtaining flocculated hydrogenated nitrile rubber; S6: soaking the flocculated hydrogenated nitrile rubber in deionized water, taking it out and drying it, so as to obtain hydrogenated nitrile rubber; S7: Completely immerse the hydrogenated nitrile rubber in the polydimethylsiloxane solution, take it out after immersion and hang it in a ventilated place to dry, and then place it in an oven for curing to obtain modified hydrogenated nitrile rubber.

[0006] Since hydrogenated nitrile rubber is obtained by hydrogenating the double bonds in nitrile rubber, this hydrogenation process reduces the unsaturated bonds in the molecule, thereby reducing the possibility of reaction with hydrogen sulfide. Hydrogenated nitrile rubber has good heat resistance and can maintain its physical and chemical properties at higher temperatures. At the same time, hydrogenated nitrile rubber also has excellent tear and wear resistance, which makes it more reliable when used in corrosive environments.

[0007] However, the acrylonitrile group in the hydrogenated nitrile rubber is a polar functional group containing a carbon-nitrogen triple bond and has a certain chemical reactivity. During oil exploration, the acrylonitrile group will react with hydrogen sulfide to form thioamide, thereby accelerating the aging and degradation of the hydrogenated nitrile rubber and reducing the corrosion resistance of the hydrogenated nitrile rubber. Since the polydimethylsiloxane solution used in the present application contains polydimethylsiloxane, the acrylonitrile group can form a cross-linked structure in the polydimethylsiloxane through reaction. This cross-linking occurs not only between the acrylonitrile groups, but also between the acrylonitrile groups and the siloxane chains of the polydimethylsiloxane, thereby forming a dense network structure on the surface of the hydrogenated nitrile rubber, making it difficult for hydrogen sulfide to enter the hydrogenated nitrile rubber and react with the acrylonitrile group, thereby improving the corrosion resistance of the hydrogenated nitrile rubber.

[0008] Preferably, a process for preparing a blowout preventer rubber core with excellent corrosion resistance comprises the following steps: S1: Weigh 148g-152g of nitrile latex with a solid content of 15%-19% and an acrylonitrile content of 32%-34% and stir; S2: Add 297g-303g of deionized water and stir, then add 5-10ml of defoamer; S3: add 0.005g-0.011g of anhydrous copper sulfate, 0.13g-0.17g of sodium dodecyl sulfate, and 225g-233g of hydrazine hydrate in sequence; S4: Add 95g-101g of hydrogen peroxide dropwise, and after the hydrogen peroxide is completely added, continue the reaction for 0.5h-1.5h to obtain hydrogenated nitrile latex; S5: placing the hydrogenated nitrile latex in a water bath at 3-7°C, adding 5 g-5.8 g of a 19%-21% calcium chloride solution to obtain flocculated hydrogenated nitrile rubber; S6: Soaking the flocculated hydrogenated nitrile rubber in deionized water for 22-26 hours, taking it out and drying it, thereby obtaining hydrogenated nitrile rubber; S7: Completely immerse the hydrogenated nitrile rubber in 136g-140g of polydimethylsiloxane solution. After soaking for 1h-2h, take it out and hang it in a ventilated place to dry. Then, place it in an oven at 55-65°C for curing for 23-25h to obtain modified hydrogenated nitrile rubber.

[0009] Preferably, the polydimethylsiloxane solution comprises the following raw materials: vinyl terminated RTV-615 type prepolymer and n-hexane.

[0010] Since acrylonitrile contains polar cyano groups, it can form weak interactions with oils and other non-polar solvents and reduce the absorption of these substances, thereby giving hydrogenated nitrile rubber good oil resistance and chemical resistance. However, acrylonitrile has certain chemical reactivity and is likely to react with hydrogen sulfide to a certain extent. The vinyl-terminated RTV-615 prepolymer contains double bonds and can be used as a cross-linking agent. Therefore, the double bonds of the vinyl-terminated RTV-615 prepolymer can react with acrylonitrile to form a cross-linking network.

[0011] Preferably, the polydimethylsiloxane solution comprises 9.8 g to 12.2 g of vinyl terminated RTV-615 type prepolymer and 124.5 to 128.5 g of n-hexane.

[0012] The amount of vinyl-terminated RTV-615 prepolymer directly affects the crosslinking density of hydrogenated nitrile rubber. Therefore, an appropriate amount of vinyl-terminated RTV-615 prepolymer can make hydrogenated nitrile rubber have an appropriate crosslinking structure.

[0013] Preferably, the vinyl terminated RTV-615 prepolymer is MOMENTIVE RTV-615 prepolymer.

[0014] Preferably, the vinyl terminated RTV-615 type prepolymer comprises a prepolymer RTV615-A and a crosslinking agent RTV615-B.

[0015] Since the prepolymer RTV615-A serves as a base polymer and provides a siloxane main chain, the heat resistance and resistance of the hydrogenated nitrile rubber are improved, and the crosslinking agent RTV615-B can react with the vinyl groups in the prepolymer RTV615-A to form crosslinking points, thereby increasing the crosslinking density of the hydrogenated nitrile rubber.

[0016] Preferably, the vinyl terminated RTV-615 type prepolymer comprises 9g-11g of prepolymer RTV615-A and 0.8g-1.2g of crosslinker RTV615-B.

[0017] Preferably, the preparation method of the polydimethylsiloxane solution is as follows: 9g-11g RTV615-A and 0.8g-1.2g RTV615-B are fully mixed, added into 124.5-128.5g n-hexane to prepare a polydimethylsiloxane solution with a mass fraction of 7-9%, and reacted for 22-26h.

[0018] Preferably, the mass ratio of the prepolymer RTV615-A to the crosslinking agent RTV615-B is 10:1.

[0019] Since an appropriate amount of cross-linking agent RTV615-B can effectively cross-link with the vinyl groups in the prepolymer RTV615-A to form a stable network structure, the mass ratio of 10:1 is beneficial to the cross-linking network of hydrogenated nitrile rubber, and the appropriate cross-linking density helps to improve the chemical resistance of hydrogenated nitrile rubber, making hydrogenated nitrile rubber suitable for more harsh environments.

[0020] In summary, this application has the following beneficial effects: 1. Since hydrogenated nitrile rubber is obtained by hydrogenating the double bonds in nitrile rubber, this hydrogenation process reduces the unsaturated bonds in the molecule, thereby reducing the possibility of reaction with hydrogen sulfide. Hydrogenated nitrile rubber has good heat resistance and can maintain its physical and chemical properties at higher temperatures. At the same time, hydrogenated nitrile rubber also has excellent tear resistance and wear resistance, which makes it more reliable when used in corrosive environments.

[0021] However, the acrylonitrile group in the hydrogenated nitrile rubber is a polar functional group containing a carbon-nitrogen triple bond and has a certain chemical reactivity. During oil exploration, the acrylonitrile group will react with hydrogen sulfide to form thioamide, thereby accelerating the aging and degradation of the hydrogenated nitrile rubber and reducing the corrosion resistance of the hydrogenated nitrile rubber. Since the polydimethylsiloxane solution used in the present application contains polydimethylsiloxane, the acrylonitrile group can form a cross-linked structure in the polydimethylsiloxane through reaction. This cross-linking occurs not only between the acrylonitrile groups, but also between the acrylonitrile groups and the siloxane chains of the polydimethylsiloxane, thereby forming a dense network structure on the surface of the hydrogenated nitrile rubber, making it difficult for hydrogen sulfide to enter the hydrogenated nitrile rubber and react with the acrylonitrile group, thereby improving the corrosion resistance of the hydrogenated nitrile rubber.

[0022] 2. Since acrylonitrile contains polar cyano groups, it can form weak interactions with oils and other non-polar solvents, reducing the absorption of these substances, thereby giving hydrogenated nitrile rubber good oil resistance and chemical resistance. However, acrylonitrile has certain chemical reactivity and is likely to react with hydrogen sulfide to a certain extent. The vinyl-terminated RTV-615 prepolymer contains double bonds and can be used as a cross-linking agent. Therefore, the double bonds of the vinyl-terminated RTV-615 prepolymer can react with acrylonitrile to form a cross-linking network.

[0023] 3. The amount of vinyl-terminated RTV-615 prepolymer directly affects the crosslinking density of hydrogenated nitrile rubber. Therefore, an appropriate amount of vinyl-terminated RTV-615 prepolymer can make hydrogenated nitrile rubber have an appropriate crosslinking structure. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with Examples 1-7 and Comparative Example 1.

[0025] raw material Nitrile latex CAS: 9003-18-3; Deionized water CAS: 7732-18-5; Anhydrous copper sulfate CAS: 7758-98-7; Sodium dodecyl sulfate CAS: 151-21-3; Hydrazine hydrate CAS: 10217-52-4; Hydrogen peroxide CAS: 7722-84-1; Calcium chloride CAS: 22691-02-7; Prepolymer RTV615-A Shenzhen Huazhisheng New Material Technology Co., Ltd.; Crosslinker RTV615-B Shenzhen Huazhisheng New Material Technology Co., Ltd.; Hexane CAS: 110-54-3.

[0026] Example Example 1 A process for preparing a blowout preventer rubber core with excellent corrosion resistance includes the following raw materials: 150g nitrile latex, 300g deionized water, 0.008g anhydrous copper sulfate, 0.15g sodium dodecyl sulfate, 229g hydrazine hydrate, 98g hydrogen peroxide, 5.4g calcium chloride solution, and 138g polydimethylsiloxane solution.

[0027] Specifically, the method for preparing a blowout preventer rubber core with excellent corrosion resistance comprises the following steps: S1: Take a 1000ml three-necked flask, weigh 150g of latex with a solid content of 17% and an acrylonitrile content of 33%, add it into the three-necked flask, turn on the stirring motor and set the speed to 260r / min for stirring; S2: Weigh 300 g of deionized water into a three-necked flask, and add 7 ml of defoamer during stirring; S3: Then, 0.008 g of anhydrous copper sulfate, 0.15 g of sodium dodecyl sulfate, and 229 g of hydrazine hydrate were added in sequence; S4: using a constant pressure funnel to drop 98 g of hydrogen peroxide, adjusting the dropping speed of the hydrogen peroxide so that the hydrogen peroxide can be added within 6 hours, and after the hydrogen peroxide is completely added, the experiment continues to react for 1 hour to obtain hydrogenated nitrile latex; S5: Pour the hydrogenated nitrile latex into a large beaker, place it in a water bath at 5°C, add 5.4 g of a 20% calcium chloride solution, and obtain flocculated hydrogenated nitrile latex; S6: Soaking the flocculated hydrogenated nitrile latex in deionized water for 24 hours, and then taking it out and drying it to obtain hydrogenated nitrile rubber; S7: 10g RTV615-A and 1g RTV615-B were fully mixed, added into 126.5g n-hexane to prepare 8% polydimethylsiloxane solution, and reacted for 24h; S8: The hydrogenated nitrile rubber is completely immersed in 138 g of polydimethylsiloxane solution. After soaking for 1.5 hours, the mixture is taken out and hung in a ventilated place to dry. Then, the mixture is placed in an oven at 60° C. and cured for 24 hours to obtain a modified hydrogenated nitrile rubber.

[0028] Example 2-3 The difference from Example 1 is that the addition amounts of the components of the blowout preventer rubber core with excellent corrosion resistance are different, as shown in Table 1.

[0029] Table 1 The amount of each component added to the blowout preventer rubber core with excellent corrosion resistance in Examples 1-3 (g)

[0030] Example 4 The difference from Example 1 is that the hydrogenated nitrile rubber is replaced by nitrile rubber; Example 5 The difference from Example 1 is that the mass ratio of the prepolymer RTV615-A to the crosslinking agent RTV615-B is 8:2.

[0031] Embodiment 6-7 The difference from Example 1 is that the added amounts of the components of the polydimethylsiloxane solution are different, as shown in Table 2.

[0032] Table 2 Addition amount of each component of polydimethylsiloxane solution in Examples 1-3 (g)

[0033] Comparative Example Comparative Example 1 The difference from Example 1 is that no polydimethylsiloxane solution is added.

[0034] Performance testing Detection Methods 1. Anti-corrosion performance test Three samples were taken from Examples 1-7 and Comparative Example 1, respectively, and the anti-corrosion performance was tested according to NACE TM0187-2011 “Standard Test Method for Evaluating Elastomeric Materials in Sour Gas Environments”.

[0035] The test data is shown in Table 3.

[0036] Table 3 Anticorrosion performance test table of Examples 1-7 and Comparative Example 1

[0037] Combining Example 1 and Comparative Example 1 and Table 3, it can be seen that, relative to Example 1, the hardness, tensile strength and elongation at break of the sample of Comparative Example 1 before hydrogen sulfide corrosion are greatly reduced, and the hardness, tensile strength and elongation at break of the sample of Example 1 after hydrogen sulfide vapor corrosion are slightly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor corrosion, compared to the slight reduction in Example 1, the hardness, tensile strength and elongation at break of the sample of Comparative Example 1 after hydrogen sulfide vapor corrosion are greatly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor corrosion, and at the same time, the mass change rate of Comparative Example 1 is greatly increased compared to the mass change rate of Example 1, which shows that the addition of polydimethylsiloxane solution can effectively improve the corrosion resistance of hydrogenated nitrile rubber.

[0038] The reason is that the acrylonitrile group in hydrogenated nitrile rubber is a polar functional group containing a carbon-nitrogen triple bond and has a certain chemical reactivity. During oil exploration, the acrylonitrile group will react with hydrogen sulfide to form thioamide, thereby accelerating the aging and degradation of hydrogenated nitrile rubber and causing the corrosion resistance of hydrogenated nitrile rubber to decline. After adding polydimethylsiloxane solution, the acrylonitrile group in hydrogenated nitrile rubber can form a cross-linked structure through reaction in polydimethylsiloxane. This cross-linking occurs not only between acrylonitrile groups, but also between acrylonitrile groups and the silicon oxygen chains of polydimethylsiloxane, thereby forming a dense network structure on the surface of hydrogenated nitrile rubber, making it difficult for hydrogen sulfide to enter the hydrogenated nitrile rubber and react with the acrylonitrile group, thereby improving the corrosion resistance of hydrogenated nitrile rubber.

[0039] In combination with Examples 1-3 and Table 3, it can be seen that, relative to Example 1, the hardness, tensile strength and elongation at break of the samples of Examples 2 and 3 before hydrogen sulfide corrosion are all reduced, and the hardness, tensile strength and elongation at break obtained by the sample of Example 1 after hydrogen sulfide vapor phase corrosion are slightly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor phase corrosion, compared to the slightly reduced in Example 1, the hardness, tensile strength and elongation at break obtained by the samples of Examples 2 and 3 after hydrogen sulfide vapor phase corrosion are all significantly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor phase corrosion, and the mass change rate of Examples 2 and 3 is all increased compared to the mass change rate of Example 1, which shows that the addition amount of each component also affects the corrosion resistance of hydrogenated nitrile rubber, and the addition amount of each component in Example 1 can obtain a hydrogenated nitrile rubber with excellent corrosion resistance.

[0040] Combining Example 1 and Example 4 and Table 3, it can be seen that, relative to Example 1, the hardness, tensile strength and elongation at break of the sample of Example 4 before hydrogen sulfide corrosion are all reduced, and the hardness, tensile strength and elongation at break of the sample of Example 1 after hydrogen sulfide vapor phase corrosion are slightly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor phase corrosion, compared to the slight reduction in Example 1, the hardness, tensile strength and elongation at break of the sample of Example 4 after hydrogen sulfide vapor phase corrosion are significantly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor phase corrosion, and the mass change rate of Example 4 is increased compared to the mass change rate of Example 1, which shows that the corrosion resistance of the rubber core obtained by reacting hydrogenated nitrile rubber with a polydimethylsiloxane solution is better than the corrosion resistance of the rubber core obtained by reacting nitrile rubber with a polydimethylsiloxane solution.

[0041] Combining Example 1 and Example 5 and Table 3, it can be seen that, relative to Example 1, the hardness, tensile strength and elongation at break of the sample of Example 5 before hydrogen sulfide corrosion are all reduced, and the hardness, tensile strength and elongation at break of the sample of Example 1 after hydrogen sulfide vapor corrosion are slightly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor corrosion, compared to the slight reduction in Example 1, the hardness, tensile strength and elongation at break of the sample of Example 5 after hydrogen sulfide vapor corrosion are significantly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor corrosion, and the mass change rate of Example 5 is increased compared to the mass change rate of Example 1, which shows that the mass ratio of the prepolymer RTV615-A to the cross-linking agent RTV615-B also affects the corrosion resistance of the hydrogenated nitrile rubber.

[0042] Combining Example 1 and Example 6-7 and Table 3, it can be seen that, relative to Example 1, the hardness, tensile strength and elongation at break of the samples of Example 6 and Example 7 before hydrogen sulfide corrosion are greatly reduced, and the hardness, tensile strength and elongation at break obtained by the sample of Example 1 after hydrogen sulfide vapor phase corrosion are slightly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor phase corrosion, compared to the slightly reduced embodiment 1, the hardness, tensile strength and elongation at break obtained by the samples of Example 6 and Example 7 after hydrogen sulfide vapor phase corrosion are significantly reduced compared to the hardness, tensile strength and elongation at break before hydrogen sulfide vapor phase corrosion, and the mass change rate of Example 6 and Example 7 is increased, which shows that the addition amount of each component of the polydimethylsiloxane solution also affects the corrosion resistance of the hydrogenated nitrile rubber, and the addition amount of each component of the polydimethylsiloxane solution in Example 1 can obtain a hydrogenated nitrile rubber with excellent corrosion resistance.

[0043] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A process for preparing a blowout preventer rubber core with excellent corrosion resistance. It is characterized in that The following steps are involved: S1: Weigh nitrile latex and stir; S2: Add deionized water and stir, then add defoamer; S3: adding anhydrous copper sulfate, sodium dodecyl sulfate, and hydrazine hydrate in sequence; S4: adding hydrogen peroxide dropwise, and after the hydrogen peroxide is completely added, the test continues to react to obtain hydrogenated nitrile latex; S5: placing the hydrogenated nitrile latex in a water bath environment, adding a calcium chloride solution, and obtaining flocculated hydrogenated nitrile rubber; S6: soaking the flocculated hydrogenated nitrile rubber in deionized water, taking it out and drying it, so as to obtain hydrogenated nitrile rubber; S7: Completely immerse the hydrogenated nitrile rubber in the polydimethylsiloxane solution, take it out after immersion and hang it in a ventilated place to dry, and then place it in an oven for curing to obtain modified hydrogenated nitrile rubber.

2. According to claim 1, a process for preparing a blowout preventer rubber core with excellent corrosion resistance, It is characterized in that The following steps are involved: S1: Weigh 148g-152g of nitrile latex with a solid content of 15%-19% and an acrylonitrile content of 32%-34% and stir; S2: Add 297g-303g of deionized water and stir, then add 5-10ml of defoamer; S3: add 0.005g-0.011g of anhydrous copper sulfate, 0.13g-0.17g of sodium dodecyl sulfate, and 225g-233g of hydrazine hydrate in sequence; S4: Add 95g-101g of hydrogen peroxide dropwise, and after the hydrogen peroxide is completely added, continue the reaction for 0.5h-1.5h to obtain hydrogenated nitrile latex; S5: placing the hydrogenated nitrile latex in a water bath at 3-7°C, adding 5 g-5.8 g of a 19%-21% calcium chloride solution to obtain flocculated hydrogenated nitrile rubber; S6: Soaking the flocculated hydrogenated nitrile rubber in deionized water for 22-26 hours, taking it out and drying it, thereby obtaining hydrogenated nitrile rubber; S7: Completely immerse the hydrogenated nitrile rubber in 136g-140g of polydimethylsiloxane solution. After soaking for 1h-2h, take it out and hang it in a ventilated place to dry. Then, place it in an oven at 55-65°C for curing for 23-25h to obtain modified hydrogenated nitrile rubber.

3. According to claim 2, a process for preparing a blowout preventer rubber core with excellent corrosion resistance, It is characterized in that The polydimethylsiloxane solution comprises the following raw materials: Vinyl terminated RTV-615 type prepolymer and n-hexane.

4. According to claim 3, a process for preparing a blowout preventer rubber core with excellent corrosion resistance, Features: The polydimethylsiloxane solution includes 9.8 g to 12.2 g of vinyl terminated RTV-615 type prepolymer and 124.5 to 128.5 g of n-hexane.

5. According to claim 4, a process for preparing a blowout preventer rubber core with excellent corrosion resistance, Features: The vinyl terminated RTV-615 prepolymer is MOMENTIVE RTV-615 prepolymer.

6. According to claim 5, a process for preparing a blowout preventer rubber core with excellent corrosion resistance, Features: The vinyl terminated RTV-615 type prepolymer comprises a prepolymer RTV615-A and a crosslinking agent RTV615-B.

7. A process for preparing a blowout preventer rubber core with excellent corrosion resistance according to claim 6, Features: The vinyl terminated RTV-615 type prepolymer includes 9g-11g of prepolymer RTV615-A and 0.8g-1.2g of crosslinking agent RTV615-B.

8. According to claim 7, a process for preparing a blowout preventer rubber core with excellent corrosion resistance, It is characterized in that The preparation method of the polydimethylsiloxane solution is as follows: 9g-11g of RTV615-A and 0.8g-1.2g of RTV615-B are fully mixed, and added into 124.5-128.5g of n-hexane to prepare a polydimethylsiloxane solution with a mass fraction of 7-9%, and react for 22-26h.

9. A process for preparing a blowout preventer rubber core with excellent corrosion resistance according to claim 8, Features: The mass ratio of the prepolymer RTV615-A to the crosslinking agent RTV615-B is 10:1.

Citation Information

Patent Citations

  • Preparation method of hydrogen sulfide-resistant anticorrosive paint and coating

    CN118725686A

  • Preparation of hydrogenated butyronitrile copolymer by hydrogenation of butadiene-acrylonitrile copolymer latex

    CN1472232A

  • Thioamide analog compound synthesis method

    CN1807409A

  • Polymer protective coated polymeric components for oilfield applications

    US20070051510A1

  • Polymeric Composites, Oilfield Elements Comprising Same, and Methods of Using Same in Oilfield Applications

    US20070142547A1